Meningkatkan Kreativitas Siswa Dengan Memanfaatkan Pewarna Makanan Dalam Pembelajaran Seni Rupa Dua Dimensi Melalui Model Discovery Learning Kelas III SDN 6 Kabila Kabupaten Bone Bolango - Febiola Bilondatu; Sukri Katili; Rustam I. Husain; La Ode Karlan; Mimy Astuty Pulukadang (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
This study aimed to improve the creativity of third-grade students at SDN 6 Kabila, Bone Bolango Regency, in two-dimensional visual arts learning through the use of food coloring integrated with the Discovery Learning model. The study employed a Classroom Action Research (CAR) design conducted in two cycles involving 18 students as the research participants. Data were collected through classroom observations, performance tests, and documentation, and were analyzed using descriptive quantitative techniques. The findings revealed a gradual improvement in students' creativity, increasing from 33% in Cycle I Meeting I to 67% in Cycle I Meeting II and reaching 78% in Cycle II, thereby exceeding the school's Minimum Mastery Criterion (MMC) of 75%. Teacher performance improved from the "Good" category to "Very Good," while student learning activities progressed from the "Fair" category to "Very Good." These findings indicate that integrating food coloring as a learning medium with the Discovery Learning model effectively enhances elementary school students' creativity in producing two-dimens